Cognitive Functions across the GNB3 C825T Polymorphism in an Elderly Italian Population. (22nd October 2013) - Casiglia, Edoardo; Giordano, Nunzia; Tikhonoff, Valérie; Boschetti, Giovanni; Mazza, Alberto; Caffi, Sandro; Guidotti, Federica; Bisiacchi, Patrizia
Abstract : To verify whether the C825T polymorphism of the GNB3 influences the response to neuropsychological tests, mini-mental state examination, digit span (DS), immediate and delayed prose memory, memory with interference at 10 and 30 seconds (MI 10 and 30), trail making tests (TMTs) A and B, abstraction task, verbal fluency (VF) test, figure drawing and copying, overlapping figures test and clock test were performed in 220 elderly men and women free from clinical dementia and from neurological and psychiatric diseases randomly taken from the Italian general population and analysed across the C825T polymorphism. The performance of DS, immediate and delayed prose memory, VF, and TMTs was worse in subjects who were TT for the polymorphism in comparison to the C-carriers. The performance of all tests declined with age. In the case of DS, immediate and delayed prose memory, MI 10 and VF, this trend was maintained in the C-carriers but not in TT. In the case of prose memory, of memory with interference, and of VF, schooling reduced the detrimental interaction between age and genotype. The C825T polymorphism of GNB3 gene therefore influences memory and verbal fluency, being additive to the effects of age and partially mitigated by schooling.